Corte Interamericana de Direitos Humanos e poder judiciário tocantinense: internalização da jurisprudência da corte como forma de aplicação dos direitos humanos e conhecimento dos tratados internacionais - Morais, Roniclay Alves (Universidade Federal do Tocantins, 2017)
The propositional research had the objective to demonstrate the importance of internalizing the Inter-American Court of Human Rights jurisprudence and stimulate Tocantinenses judges to be in touch with the international human rights treaties. This research is justified by the importance of the subject understood as essential to judge. The method quanti-qualitative was the most appropriate to reach the objectives proposed to find the level of knowledge of Tocantinenses judges of the Court decisions and the use of Its jurisprudence. The data survey was done by 10 demi-opened questions applied between the months of March and June in 2016. These questions was answered by 86 judges from a total of 130 that still work nowadays. Beyond the results acquired from the questionnaire application it was also used a huge amount of bibliographic material through searches in books, scientific articles, legislation and internet web sites. The results indicate the necessity to foment the knowledge of judges concerning the observance of international treaties and, mainly, the internalization of the Court jurisprudence as a way to make sure the application of Human Rights.